Market for patents, monopoly, and misallocation - WEI, Shang-jin (Institutional Knowledge at Singapore Management University, 2023)
The paper studies a possible “dark side” of patent trade in enhancing the market power of monopolists. We explore the different effects of China’s 2008 tax reform on patent innovations and sales across industries. In particular, although easier patent trade leads to more patent creation, the new patents are disproportionately connected to existing monopolists and are more likely to be acquired by them. Using an endogenous growth model with patent trade, we show that subsidizing patent trade could skew investors’ research to appeal to the monopolists, increase the latter’s monopoly power, and reduce social welfare. An optimal subsidy policy for patent trade should be contingent on the initial level of misallocation in the invention market.